Village Community Creativity Through IT (Case Study of SMP Plus Bina Terampil Desa Sukasari Kecamatan Rumpin Bogor) - Edison Hotaguan Manurung; Herbert Hasudungan Siahaan; Kasimir Sawito; Bantu Hotsan Simanullang; Rizki Abdullah; Ikbal Iskandar; Fatimah Marthaliza; Safrianus Hardi Farno; Ilham Laia; Agus Sulaeman (Indonesian Journal of Advanced Social Works, 2022)
Technological developments in the 4.0 era have shot up. Almost all activities are carried out digitally. Some things that used to be done manually are now being done with a computer, such as drawing which used to be done using a pencil, now drawing can be done using a computer. Through this KKN program, we want to teach students of SMP Plus Bina Skilled, Sukasari Village, Rumpin District, Bogor Regency, how to draw/design posters through the Canva application. This poster design can not only be for business, but used in other fields such as invitation posters or event posters.